2012
DOI: 10.4161/auto.19048
|View full text |Cite
|
Sign up to set email alerts
|

Methylthioninium chloride (methylene blue) induces autophagy and attenuates tauopathy in vitro and in vivo

Abstract: aldehyde phosphatase dehydrogenase; GSK-3, glycogen synthase kinase 3; GFP, green fluorescent protein; Hsc, heat shock cognate; Hsp, heat shock protein; IGF, insulin-like growth factor; IRS, insulin receptor substrate; MB, methylene blue; LC, liquid chromatography; MS, mass spectroscopy; mTOR, mammalian target of rapamycin; PI3, phosphoinositide 3-kinase; PBS, phosphate buffered saline; p70, p70S6 kinase; pp70, phosphorylated p70S6 kinase; RFP, red fluorescent protein; shRNA, short hairpin RNA More than 30 neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
200
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 275 publications
(211 citation statements)
references
References 48 publications
11
200
0
Order By: Relevance
“…Although these reports apparently contradict earlier in vitro studies showing that MB can inhibit Tau aggregation (67,68), there have been accumulating positive reports using Tau transgenic mice and other systems (e.g. primary neuronal or organotypic slice cultures) that confirm the original observations (70,71). Given this apparent effect of MB on Tau, the compound's use as an AD therapeutic has been evaluated.…”
Section: Discussionmentioning
confidence: 78%
“…Although these reports apparently contradict earlier in vitro studies showing that MB can inhibit Tau aggregation (67,68), there have been accumulating positive reports using Tau transgenic mice and other systems (e.g. primary neuronal or organotypic slice cultures) that confirm the original observations (70,71). Given this apparent effect of MB on Tau, the compound's use as an AD therapeutic has been evaluated.…”
Section: Discussionmentioning
confidence: 78%
“…To identify the potential mechanism by which MB inhibited necrosis, we focused on the effect of MB on mitochondrial structure and function after stroke, considering that the mitochondrion is an important target of MB (50). The observation and scoring of the mitochondrial ultrastructure indicated that the mitochondrial structure was seriously disrupted after stroke, but that MB dramatically ameliorated the disintegration of the mitochondrial structure.…”
Section: Discussionmentioning
confidence: 99%
“…7,11 In cellular models, inhibitors of the ATPase activity of Hsp70 have been shown to favor tau turnover and "re-set" its homeostasis. 12 Moreover, first-generation Hsp70 inhibitors, such as methylene blue (MB), improve learning and memory in mouse models of tauopathy, 13,14 suggesting that this strategy holds promise for the eventual treatment of AD and other tauopathies.…”
mentioning
confidence: 99%